Sexual risk behaviour among school-going adolescents in Sierra Leone and Liberia: a secondary analysis of the 2017 Global school-based student health surveys - Peter Bai James; Augustus Osborne; Abdulai Jawo Bah; Emmanuel Kamanda Margao; Mohamed Conteh-Barrat (BMC, 2022)
Abstract Background Sierra Leone and Liberia have experienced civil wars and, recently, Ebola outbreaks that led to profound economic hardship, psychopathologies and family disruptions. These factors are associated with sexual risk behaviours among youths. However, there is very little information on sexual risk behaviour among Sierra Leonean and Liberian school-going adolescents. The present study assessed the prevalence and determinants of sexual risk behaviours among school-going adolescents (10-19 years) in Sierra Leone and Liberia.  Method We used publicly available nationally representative cross-sectional datasets of the 2017 Sierra Leone and Liberia Global school health survey. The sample consisted of 2798 and 2744 school-going adolescents from Sierra Leone and Liberia, respectively. Complex sample descriptive and regression analysis was used to analyse our data. Results The majority of adolescents in the two countries were involved in multiple sexual risk behaviour (80.2%), with a higher prevalence observed in Sierra Leone (85.2%) than in Liberia (75.3%). Liberian adolescents showed lesser odds of indulging in multiple sexual risk behaviours than their Sierra Leonean counterparts (AOR = 0.572; 95%CI: 0.345-0.946). Male, compared to females, were more likely to engage in multiple sexual risk behaviour (AOR = 2.310;95%CI:1.543-3.458), with a similar pattern observed in both countries. Alcohol use was associated with multiple sexual risk behaviour (AOR = 3.064; 95%CI: 2.137-4.392). Also, in Sierra Leone and Liberia, adolescents with one and two or more forms of psychological distress were more likely to have ever had sex than those who did not show any form of psychological distress. Missing class/school was associated with multiple sexual risk behaviour (AOR = 1.655; 95%CI:1.133-2.418). Peer support was only found to be a protective factor against no condom use among Liberian adolescents (AOR = 0.608; 95%CI: 0.435-0.850). Less parental support was only associated with ever had sex among adolescents in Sierra Leone (AOR = 2.027; 95%CI: 1.322-3.107) but not in Liberia (AOR = 1.034; 95%CI: 0.650-1.644). Conclusion Our study found a high sexual risk behaviour among school-going adolescents in Sierra Leone and Liberia. Our finding highlights the need to strengthen sexual and reproductive health education in schools and communities that incorporate mental health promotion activities tailored to this group.